Pengembangan Sistem Informasi Kesehatan Sekolah untuk Meningkatkan Peran UKS MA Mannilingi Bulo-Bulo - Hartini Ramli; Mihrani Mihrani; Dian Ayu Lestari; Muhammad Asmaul Husnaa; Desriani Thalia Pabontong (Indonesian Technology and Education Journal, 2024)
Health plays an important role in the world of education, especially in the school environment. Schools have a significant role to play in health research and efforts to improve health in young people. The School Health Unit (UKS) is one of the government's ways to improve the health level of the community in the school environment. For example, in Jeneponto District there is the Mannilingi Bulo-Bulo MA school which has a UKS program. The UKS program at these schools makes a positive contribution in overcoming school community health problems, which in turn improves the quality of education and student achievement in the environment. Nonetheless, the UKS program still needs to be improved because currently its implementation is still manual and it is experiencing problems in incomplete data collection. Therefore, a solution is needed in the form of developing a school health information system to increase the effectiveness and efficiency of UKS services and overcome the problem of suboptimal data collection. The research methods to be used in building this system include observation, literature study, and system development methods with a prototyping approach. The implementation of a school health information system is expected to increase the effectiveness and efficiency of UKS services and overcome the problem of incomplete data collection.